Pengaruh Green Marketing Dan Social Media Marketing Terhadap Keputusan Pembelian (Survey pada Produk Ramah Lingkungan AQUA di Lingkungan Mahasiswa Fakultas Ekonomi & Bisnis UNISMA Angkatan 2020) - Kirana, Denny Candra; Diana, Nur; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to examine the factors influencing the purchase decision of environmentally friendly AQUA products. The focus of this research is on two independent variables: green marketing and social media marketing. This study employs a quantitative research approach with the distribution of questionnaires. The survey includes 94 participants, and the data analysis is conducted through the Smart-PLS software. The study has fulfilled the requirements for both validity and reliability. Data analysis used in this study includes descriptive statistical method tests, linearity tests, partial least square (PLS): Measurement Model (Outer Model), Structural Model (Inner Model), and hypothesis testing. The variables used in this study are Purchase Decision (dependent variable), green marketing, and social media marketing (independent variables). The results of this study conclude that the green marketing variable has a significant influence on purchase decisions, while the social media marketing variable does not have an influence on purchase decisions. Keywords: Purchasing Decision, Green Marketing, Social Media Marketing.